Improving growth of Clinacanthus Nutans using modified clinoptilolite zeolite - Noor Hidayah Dzkulfli, 1989-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Thesis (Sarjana Sains (Biosains)) - Universiti Teknologi Malaysia, 2015